2020
DOI: 10.14569/ijacsa.2020.0110605
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of EIGRP and OSPF Protocols based on Network Convergence

Abstract: Dynamic routing protocols are one of the fastest growing routing protocols in networking technologies because of their characteristics such as high throughput, flexibility, low overhead, scalability, easy configuration, bandwidth, and CPU utilization. Albeit convergence time is a critical problem in any of these routing protocols. Convergence time describes summary of the updated, complete, and accurate information of the network. Several studies have investigated EIGRP and OSPF on the internet; however, only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Figure 2 illustrates how network virtualization uses mapping algorithms to optimally allocate virtual resources across the physical infrastructure. Virtual network operators use mapping algorithms to decide to request certain virtual resources from the VNP, which are then instantiated by the underlying InPs [16]. Virtual network mapping allocates virtual resources to nodes and links and can be divided into two subproblems: virtual node mapping, i.e., mapping all virtual nodes to the corresponding physical nodes, and virtual link mapping, i.e., mapping the virtual links connecting virtual nodes to the physical links connecting physical nodes accordingly.…”
Section: Application Of Optimal Subnetwork-basedmentioning
confidence: 99%
“…Figure 2 illustrates how network virtualization uses mapping algorithms to optimally allocate virtual resources across the physical infrastructure. Virtual network operators use mapping algorithms to decide to request certain virtual resources from the VNP, which are then instantiated by the underlying InPs [16]. Virtual network mapping allocates virtual resources to nodes and links and can be divided into two subproblems: virtual node mapping, i.e., mapping all virtual nodes to the corresponding physical nodes, and virtual link mapping, i.e., mapping the virtual links connecting virtual nodes to the physical links connecting physical nodes accordingly.…”
Section: Application Of Optimal Subnetwork-basedmentioning
confidence: 99%
“…When the waiting period exceeds beyond 10 seconds the standby router takes up the active job of packet transfer. Here, the priority of the active router is removed due to router failure and standby router's priority becomes the highest in the HSRP group [9]. During this switch over, nearly 2-3 packet loss was observed.…”
Section: Test Case #1: When Active/standby Hsrp Router Failsmentioning
confidence: 97%
“…Apart from this, to have better flexibility in the network, implementation of dynamic routing protocols is necessary for increasing throughput, bandwidth, scalability that reduces the CPU utilization and convergence time. Okonkwo and Emmanuel, (2020) [9] made a comparative study between EIGRP and OSPF by implementing star and mesh network topology. The experiment showed that EIGRP gave higher performance for checking the link failure and adding new links as per the network requirement.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…VLSMs allow you to granularly assign essential bits of the host. The main characteristic of the routing protocol is its unequal load balancing [26]. The routing protocol of EIGRPv6 has 3 tables that aid in routing decisions [27].…”
Section: Eigrpv6mentioning
confidence: 99%